Complex cytogenetic and molecular-genetic analysis of males with spermatogenesis failure - Huleyuk, N.; Zastavna, D.; Tyrkus, M.; Makukh, H.; Gavrylyshyn, S.; Kurpisz, M. (Цитология и генетика, 2010)
The chromosomal anomalies, microdeletions of AZF region of Y-chromosome and CFTR gene mutations have been studied among 80 infertile men with idiopathic spermatogenetic failure: 36 (45 %) patients with aspermia, 19 (24 %) patients with azoospermia and 25 (31 %) patients with severe oligoasthenoteratozoospermia. In total 30 % males with spermatogenetic failure genetic factor of infertility was observed. Karyotype anomalies were observed in 17.5 % of infertile men, within 16.2 % numerical and structural gonosomal anomalies and in 1.3 % – Robertsonian translocation were revealed. In 11 % males with spermatogenetic failure, Y-chromosome AZF region microdeletions were detected. The frequency of CFTR major mutation F508del among infertile men was 6.25 %. 5T allele of polymorphic locus IVS8polyT was detected in 7.5 % of examined men. The results obtained indicate the high complexity of cytogenetic and moleculargenetic studies of male infertility.